Successful alternative treatment of extensively drug-resistant tuberculosis in Argentina by a combination of linezolid, moxifloxacin and thioridazine - Abbate, Eduardo (2012)
Objectives: Current drug choices to treat extensively drug-resistant (XDR) tuberculosis (TB) are scarce; therefore, information on the safety, tolerability and efficacy of alternative regimens is of utmost importance. The aim of this study was to describe the management, drug adverse effects and outcome of alternative combined treatment in a series of XDR-TB patients. Patients and methods: A retrospective study was performed on 17 non-AIDS, pulmonary adult patients with XDR-TB admitted to a referral treatment centre for infectious diseases in Buenos Aires from 2002 through 2008. Drug susceptibility testing was performed under regular proficiency testing and confirmed at the national TB reference laboratory. Results: Linezolid was included in the drug regimens of all patients; moxifloxacin and/or thioridazine were included in the regimens of 14 patients. Clinically tractable drug adverse effects were observed in nine patients, the most frequent being haematological disorders and neurotoxicity. In two patients, thioridazine was discontinued. Negative culture conversion was achieved in 15 patients, 11 completed treatment meeting cure criteria, 4 are still on follow-up with good evolution, 1 defaulted treatment and 1 was lost to follow-up. Conclusions: The combination of linezolid, moxifloxacin and thioridazine is recommended for compassionate use in specialized centres with expertise in the management of XDR-TB.